Large Magnetoresistance in Scandium Nitride Magnetic Tunnel Junctions Using First Principles. Issue 11 (4th October 2021) - Karki, Suyogya; Rogers, Vivian; Jadaun, Priyamvada; Marshall, Daniel S.; Incorvia, Jean Anne C.
Abstract: The state‐of‐the‐art magnetic tunnel junction, a cornerstone of spintronic devices and circuits, uses a magnesium oxide tunnel barrier that provides a uniquely large tunnel magnetoresistance at room temperature. However, the wide bandgap and band alignment of magnesium oxide‐iron systems increases the resistance‐area product and creates variability and breakdown challenges. Here, the authors study using first principles narrower‐bandgap scandium nitride (ScN) transport properties in magnetoresistive junctions in comparison to magnesium oxide. The results show a high magnetoresistance in Fe/ScN/Fe via Δ1 and Δ 2 ′ symmetry filtering with low wave function decay rates, suggesting scandium nitride could be a new barrier material for spintronic devices. Abstract : First principles are used to study narrower‐bandgap scandium nitride (ScN) as a tunnel barrier material for magnetic tunnel junction devices, in comparison to state‐of‐the‐art magnesium oxide. The results show a high magnetoresistance in Fe/ScN/Fe via Δ1 and Δ 2 ′ symmetry filtering with low wave function decay rates, suggesting scandium nitride could be a new barrier material for spintronic devices.